2012
DOI: 10.1152/jn.00251.2012
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of thalamic auditory neurons by the primary auditory cortex

Abstract: Tang J, Yang W, Suga N. Modulation of thalamic auditory neurons by the primary auditory cortex. J Neurophysiol 108: [935][936][937][938][939][940][941][942] 2012. First published May 2, 2012; doi:10.1152/jn.00251.2012.-The central auditory system consists of the lemniscal and nonlemniscal pathways or systems, which are anatomically and physiologically different from each other. In the thalamus, the ventral division of the medial geniculate body (MGBv) belongs to the lemniscal system, whereas its medial (MGBm) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Another intriguing possibility is that changes may occur initially in the AC and are then transmitted to the IC via descending projections (Figure 1 ). There is extensive evidence to suggest that descending corticofugal projections are not only involved in short-term modulation of auditory processing but long-term changes as well, and have specifically been implicated in gain control ( 80 83 ). Indeed, inactivation of the AC has been shown to modulate firing rates and rate-level functions in the IC in a complex manner ( 75 ).…”
Section: Gain Enhancement In the Central Auditory Systemmentioning
confidence: 99%
“…Another intriguing possibility is that changes may occur initially in the AC and are then transmitted to the IC via descending projections (Figure 1 ). There is extensive evidence to suggest that descending corticofugal projections are not only involved in short-term modulation of auditory processing but long-term changes as well, and have specifically been implicated in gain control ( 80 83 ). Indeed, inactivation of the AC has been shown to modulate firing rates and rate-level functions in the IC in a complex manner ( 75 ).…”
Section: Gain Enhancement In the Central Auditory Systemmentioning
confidence: 99%
“…As in the midbrain, electrical stimulation studies have shown that corticofugal modulation can alter the receptive field properties of neurons in the auditory thalamus (Tang, Yang & Suga, ; Zhang & Suga, ). Furthermore, recent work has shown that the receptive fields of neurons in the visual sector of cat TRN (i.e., the perigeniculate nucleus) are comparable to those of LGN neurons (Soto‐Sánchez, Wang, Vaingankar, Sommer & Hirsch, ).…”
Section: Context‐dependent Modulation Of Thalamic Sensory Processingmentioning
confidence: 99%
“…The implication for these intersecting feedforward and feedback circuits is that the output signal at any station will be the collective sum of the ascending activity along with the modifications from direct and polysynaptic links from above. Feedback circuits could sharpen frequency tuning curves (Yan et al, ; Tang et al, ), calibrate directional selectivity (Zhou and Jen, ; Nakamoto et al, ), modulate response features (Ma and Suga, ; Yan and Ehret, ), or unmask acoustic signals in a noisy background (Nieder and Nieder, ). A better understanding of the details of these descending projections will inform us of possible mechanisms of action.…”
mentioning
confidence: 99%